Executive Committee Minutes 2012-10-18 - Academic Senate:::::::::
Agenda approved. Minutes delayed. Chair Report. President Report. Provost Report. Changes to the BS in Business Administration. Statewide Senator Report. Vice Chair Report. Chief Student Affairs Officer Report. Discussion of bike/skateboard safety and enforcement for referral to committee – referred to SAC. SAC Report. Associated Students Report. Senate agenda approved.